Social Interaction of Class IV Elementary School Students During the Covid-19 Pandemic - Afriani, Mayang; Ramadan, Zaka Hadikusuma (Universitas Pendidikan Ganesha, 2021)
Students also experience the impact of Covid-19 by limiting social interaction. However, social interaction is needed for a child to build character and social skills in interacting with other people. This study aimed to analyze patterns of social interaction in the fourth grade COVID-19 period in elementary school. The research subjects were 3 teachers and 90 students. The research instruments are interviews and questionnaires. The data collection technique used in this study was non-test, namely a questionnaire (questionnaire) and interviews. The results showed that social interaction during the pandemic was less effective. As evidenced by the five indicators, working together has an average score of 82.43%; during a pandemic, it is less effective due to limitations and many obstacles. The openness of the average value of 82.43% is classified as